Factors Related to Caring for Children with Congenital Heart Disease After Heart Surgery Among Caregivers - Khueanthong , Phiset; Jintrawet , Usanee; Klunklin , Pimpaporn (Nursing Journal CMU, 2021)
Caring for children with acyanotic congenital heart diseases (CHDs) after open-heart surgery by caregivers at home is important for the children’s health. This The purpose of this correlational descriptive research was to study caring for children with CHDs after heart surgery, and the relationship between perception of health status of children with CHDs, after heart surgery, and the perceived self-efficacy in caring for children with CHDs after heart surgery and caring for children with CHDs after heart surgery among caregivers. The sample comprised 85 caregivers providing care for children aged 1-6 years with CHDs at home after heart surgery with less not more than 30 days after heart surgery. Data were collected at the out-patient department of three tertiary hospitals in the northern region and a the Heart Center in the northeast region of Thailand from March to July 2019. The research instruments, including included the perception of health status of children with CHDs after heart surgery questionnaire, the perceived self-efficacy in caring for children with CHDs after heart surgery questionnaire, and the caring for children with CHDs after heart surgery questionnaire. Data were analyzed using descriptive statistics and Pearson’s product-moment correlation coefficient. The results were as follows: Caregivers of About 71.80% of the caregivers who provided care for children with CHDs after heart surgery had mean scores of caring at a high level (▁x=92.02, S.D.=12.98) The perception of health status was statistically significant positive correlation with caring for children with CHDs after heart surgery at a moderate level (r=0.538, p<.001), and perceived self-efficacy in caring for children was statistically significant positive correlation with caring for children with CHDs after heart surgery at a high level(r=0.846, p<.001). There were significantly positive correlation between the perception of health status and the caring for children with CHDs after heart surgery at a moderate level (r=0.538, p<.001), and significantly positive correlation between the perceived self-efficacy and the caring for children with CHDs after heart surgery at a high level (r=0.846, p<.001). The findings of this study serve as preliminary data and provided related factors for a guide to promote the caring for children with CHDs after heart surgery among caregivers.